2020
DOI: 10.1186/s10020-020-00221-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 alleviates the capillary leakage and inflammation in sepsis

Abstract: Background Acute lung injury (ALI), which is induced by numerous pathogenic factors, especially sepsis, can generate alveolar damage, pulmonary edema and vascular hyper-permeability ultimately leading to severe hypoxemia. Fibroblast growth factor-2 (FGF2) is an important member of the FGF family associated with endothelial cell migration and proliferation, and injury repairment. Here, we conducted this study aiming to evaluate the therapeutic effect of FGF2 in sepsis-induced ALI. Methods Recombinant FGF2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…iTE-scaffold abolished the cytokine storms and distinctly stimulated the secretion of pro-healing factors (IL-10 and TGF-β), suggesting a better bone repair potential of the iTE-scaffold. It was reported that bFGF dampened the pro-inflammatory factors production and converted LPS-stimulated inflammatory macrophages polarization into M2 phenotype through AKT/P38/NF-κB pathway [ 16 ]. Furthermore, P-scaffold had no significant effect on reversing LPS-induced M1 macrophages and secretion of inflammatory factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…iTE-scaffold abolished the cytokine storms and distinctly stimulated the secretion of pro-healing factors (IL-10 and TGF-β), suggesting a better bone repair potential of the iTE-scaffold. It was reported that bFGF dampened the pro-inflammatory factors production and converted LPS-stimulated inflammatory macrophages polarization into M2 phenotype through AKT/P38/NF-κB pathway [ 16 ]. Furthermore, P-scaffold had no significant effect on reversing LPS-induced M1 macrophages and secretion of inflammatory factors.…”
Section: Resultsmentioning
confidence: 99%
“…It is an essential growth factor (GF) in wound healing because of its benefits as a powerful inducer of vascularization [ 13 ], proliferation [ 14 ], and migration [ 15 ]. Recently, Pan et al discovered that bFGF could reduce the production of pro-inflammatory factors and promoted lipopolysaccharide (LPS)-stimulated inflammatory macrophages polarization towards anti-inflammatory M2 phenotype through AKT/P38/NF-κB signaling pathways [ 16 ]. Another study reported that bFGF could suppress LPS-mediated inflammatory responses in periodontal ligament stem cells (PDLSCs) ex vivo [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, FGF2 was found to prevent the neuroinflammation-induced decrease in the phosphorylation of ERK1/2 and alleviated the neuroinflammation-induced impairment in hippocampal neurogenesis (35). In another study, FGF2 improved the survival rate of septic mice by inhibiting the inflammatory response, alleviating lung injury (36). Moreover, FGF2 was reported to stimulate the migration and proliferation of endothelial cells in vivo and to relieve inflammation by inducing the expression of inflammation-related genes, such as proinflammatory cytokines and chemokines in endothelial cells (36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…In another study, FGF2 improved the survival rate of septic mice by inhibiting the inflammatory response, alleviating lung injury (36). Moreover, FGF2 was reported to stimulate the migration and proliferation of endothelial cells in vivo and to relieve inflammation by inducing the expression of inflammation-related genes, such as proinflammatory cytokines and chemokines in endothelial cells (36)(37)(38). In human DPCs, FGF2 was demonstrated to induce the expression of chemokines, such as IL-6, IL-8, monocyte chemoattractant protein-1α (MIP-1α) and MIP-3α (31).…”
Section: Discussionmentioning
confidence: 97%
“…miR-26a-5p, through the reduction in connective tissue growth factor, protected mice with lung injury from lipopolysaccharide (LPS, i.e., endotoxin) by decreasing the severity of inflammation [46]. Finally, fibroblast growth factor 2 and phospholipase D2 have been reported to stabilize VE-cadherin-the former by inhibiting pro-inflammatory pathways, and the latter by preventing VE-cadherin phosphorylation-thereby improving pulmonary endothelial barrier permeability [47,48].…”
Section: Figurementioning
confidence: 99%